Policy networks and policy change putting policy network theory to the test - Compston, Hugh 1955- (Palgrave Macmillan, 2009)
"This study applies policy network theory to major technological, economic, environmental and social trends to generate propositions about the future of public policy. Among the findings are that we should expect more business-friendly policies, more intrusive law enforcement, more women-friendly policies, and stronger climate policies"--Provided by publisher